Bioremediation of Crude Oil by Different Fungal Genera (Asian Journal of Plant Biology, 2014)
One of the major environmental problems today is hydrocarbon contamination resulting from the activities related to the petrochemical industry. Bioremediation is the promising technology for treatment of these contaminated sites as it is cost effective and lead to complete mineralization. This research attempts to study the potential of different fungal genera in bioremediation of hydrocarbon. Aspergillus flavus, Aspergillus versicolor, Bionectria ochroleuca, Penicillium chermisinum and Trichoderma virens was selected for the bioremediation purpose. Screening of fungi species sensitivity towards hydrocarbons was first conducted. To enhance the growth of fungi on hydrocarbon contaminated soil, suitable bulking agent was selected prior to addition into the soil. For the period of six weeks, hydrocarbon degradation trial was conducted followed by post-treatment tests. All fungal species shows high tolerance towards hydrocarbon. Sago waste (sago hampas) is the most suitable bulking agent as all fungal species capable to grow on it. Significant differences were found in the ability of Bionectria ochroleuca to degrade hydrocarbon. Bionectria ochroleuca was able to degrade more than 70 % of the C12 to C28, with 100 % degradation of C12 and C28.
Keywords: Bioremediation, Hydrocarbon, sago hampas, Bionectria ochroleuca